STUDI KELARUTAN SCALE SEPARATOR PLTP DIENG DENGAN LARUTAN H2O2, HNO3, DAN HF SERTA PENGARUH EFEK MEKANIK - Rahim, Yusuf
Geothermal energy is a promising source of renewable energy for electricity, especially to Indonesia, which has aproximately one third of the world resources, approximately 276 potential sites to be PLTP. However, many obstacles that hinder Indonesian government's desire to make geothermal energy as an excellent source of energy for the nation as well as the pride in the eyes of the world. Besides the issue of fund and human resources, there is also the main technical problem that became the scourge of the world geothermal Indonesia, the scaling problem. The formation of material deposits on the surface of a construction. In this study, the formation of scale on the PLTP Dieng’s separator is selected as the main case of the research and the scale on the seperator is the sample that is was studied. The study began with characterizing the samples using a macro camera and SEM to see the morphology of the sample and to obtain type of compounds and elements, XRD and EDS characterization were done. Knowing the type of compound born within the sample, then H2O2, HNO3, and HF were determined as solvent to see the dissolution of the sample scale in each solvent. The study also extended to see the effect of variations in the concentration of the solution, the temperature of dissolution, and the dissolution time that were done in a static state. In addition to solubility test in a static state, the effects of mechanical effect at the time of dissolution is observed by dissolving it on a magnetic stirer. The corrosivity of the three solvents on carbon steel were also observed. The results of this study indicate only HF solution could dissolve the scale significantly, obtained up to 5.53% weight reduction in the static test and 14.18% in the dynamic test. This fits with the result of EDS characterization that showed there were elements of Si and O as the main contentof the scale. Although the XRD result showed the Silica (SiO2) was in amorphous state and which can be dissolved in HF. Nevertheless, the corrosivity of HF for cabon steel is still too high, reaching 12.46mm/year. While H2O2 has the smallest corrosivity, which is only 0.55mm/year. Keywords: Scaling, geothermal power plant (PLTP), H2O2, HNO3, HF, corrosion